PENGARUH KEPUASAN KERJA, KOMUNIKASI, SEMANGAT KERJA DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA PEGAWAI DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN LAHAT - JHON PERLI LOVIE (Jurnal Manajemen dan Bisnis, 2021)
The significant test of the effect of Job Satisfaction (X1) on Job Performance (Y) obtained a Sig value of 0.000 <0.05, then Ha is accepted and Ho is rejected. Thus Job Satisfaction (X1) has a significant effect on Job Performance (Y). Significant test of the influence of Communication (X2) on Work Performance (Y) obtained a Sig value of 0.000 <0.05, then Ha is accepted and Ho is rejected. Thus the influence of Communication (X2) on the Work Achievement variable (Y) can be said to have a significant influence. Significant test of the 2effect of work spirit (X3) on the work achievement variable (Y) obtained a Sig value of 0.006 <0.05, then Ha is accepted and Ho is rejected. Thus, the influence of Work Morale (X3) on the Work Achievement variable (Y) can be said to have a significant influence. The significant test of the effect of Work Discipline (X4) on Work Performance (Y) obtained a Sig value of 0.026 <0.05, then Ha is accepted and Ho is rejected. Thus the effect of Work Discipline (X4) on the Work Achievement variable (Y) can be said to have a significant influence. Significant value 0.000 <0.05, thus Ho is rejected and Ha is accepted, meaning that the variable Job Satisfaction (X1), Communication (X2) , Work Morale (X3) and Work Discipline (X4) together have a significant influence on the Work Achievement variable (Y).